The mediating role of self-advocacy in family cohesion and adaptability and health promotion in breast cancer survivors - Li Qian; Yan Li; Dan Yue (Frontiers in Medicine)
BackgroundBreast cancer is the most common cancer among women. Health-promoting behaviors can enhance the quality of life for breast cancer survivors; however, further research is needed to identify the factors influencing these behaviors.MethodsA survey was conducted on 238 breast cancer survivors from a tertiary hospital in Chongqing using a general information questionnaire, the Family Cohesion and Adaptability Scale, the Self-Advocacy Scale, and the Health-Promoting Lifestyle Profile II. Descriptive analysis was performed using SPSS 26.0, and the mediating effect of variables was analyzed using the structural equation model in SPSS AMOS 24.0.ResultsThe model results revealed positive correlations between family cohesion and adaptability and self-advocacy (β = 0.55; p < 0.05), between family cohesion and adaptability and health promotion (β = 0.42; p < 0.05), and between self-advocacy and health promotion (β = 0.43; p < 0.05) among breast cancer survivors. Furthermore, self-advocacy partially mediated the relationship between family cohesion and adaptability and health-promoting lifestyles (β = 0.237; p < 0.05).ConclusionSelf-advocacy is a mediator variable in the relationship between family cohesion and adaptability, and the health-promoting lifestyle of breast cancer survivors.